2013
DOI: 10.1007/s12070-013-0655-5
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Hypotension for Functional Endoscopic Sinus Surgery: Comparison of Esmolol and Nitroglycerine

Abstract: Intraoperative bleeding causing poor visibility of surgical field is of major concern during functional endoscopic sinus surgery (FESS) and impaired visibility may result in many complications. The study aimed to compare surgical conditions for FESS during controlled hypotension provided by esmolol or nitroglycerine (NTG) under general anaesthesia. 52 adult patients of both sexes requiring FESS under general anaesthesia were randomly divided to receive either esmolol (group ESM, n = 26) or NTG (group NTG, n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 11 publications
(16 reference statements)
3
49
0
2
Order By: Relevance
“…13 In our study, the placebo group required vasodilators to achieve hypotension in few cases. But none of the patients in clonidine group required vasodilators.…”
Section: Discussionmentioning
confidence: 84%
“…13 In our study, the placebo group required vasodilators to achieve hypotension in few cases. But none of the patients in clonidine group required vasodilators.…”
Section: Discussionmentioning
confidence: 84%
“…However, vasoactive drugs cannot reduce the FESS bleeding when MAP was controlled at level of 65-75 mmHg (17); conversely, vascular dilation caused by the drug would increase surgical bleeding and has a negative impact on the surgical field (14). Previous studies have demonstrated a significant correlation between the HR and surgical field bleeding during surgery (18)(19)(20). Compared with nitroglycerin, esmolol reduces bleeding by slowing down HR and offering an improved surgical approach with only minimal reduction in MAP (18).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated a significant correlation between the HR and surgical field bleeding during surgery (18)(19)(20). Compared with nitroglycerin, esmolol reduces bleeding by slowing down HR and offering an improved surgical approach with only minimal reduction in MAP (18). Therefore, FESS should be performed at a lower level of HR (20) as controlling HR is more effective on improving the surgical approach than lowering MAP.…”
Section: Discussionmentioning
confidence: 99%
“…But reflex tachycardia associated with NTG partially offset the advantage of induced hypotension 3,9 . Beta blockers like Metoprolol, Labetalol and Esmolol were used preoperatively to control the heart rate in view of reducing blood loss 10,11,12 . Clonidine, a centrally acting α 2 agonist is not only antihypertensive but has analgesic, sedative, anxiolytic properties.…”
Section: Discussionmentioning
confidence: 99%